2012
DOI: 10.1017/jfm.2012.362
|View full text |Cite
|
Sign up to set email alerts
|

Transition scenario of a sphere freely falling in a vertical tube

Abstract: The paper presents the results of direct numerical simulations of the fall of a single freely moving sphere in a vertical circular tube. Most results are obtained for the solid–fluid density ratio ${\rho }_{s} / \rho = 2$. The parametric investigation is carried out depending on the Galileo number defined in Jenny, Dušek & Bouchet J. Fluid Mech., vol. 508, 2004, pp. 201–239. A qualitatively new scenario is found, as compared to that of an unconfined sphere. The primary bifurcation making the sphere deviate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…ρ f , and the Galileo number or "Archimedes number." 17 The Galileo number is defined as [17][18][19][20]…”
Section: The Problem Descriptionmentioning
confidence: 99%
“…ρ f , and the Galileo number or "Archimedes number." 17 The Galileo number is defined as [17][18][19][20]…”
Section: The Problem Descriptionmentioning
confidence: 99%
“…Wake instabilities of the later kind have already been reported by Newton [1] when studying the drag of spheres in falling liquids. Over the last 15 years, with the advent of direct numerical simulation (DNS) at higher Reynolds number and high speed imaging techniques, this problem has received renewed attention [2,3,4,5,6,7]. A big variety of motions have been reported for such a system, a review on this subject can be found in [8] and a detailed historical review in [4].…”
Section: Introductionmentioning
confidence: 99%
“…Available turbulence models include the widely used Spalart-Allmaras and A'-«j-Shear Stress Transport (SST) models. The chimera approach is also implemented [23,24]. Validations have been presented at the AIAA validation workshop series, namely drag predictions [25], high lift [26] and aeroelastic [27], and in a number of European framework program reports [28].…”
Section: B Navier-stokes Solvermentioning
confidence: 99%